Tantangan Implementasi Sertipikat Tanah Elektronik di Kementerian Agraria dan Tata Ruang/Badan Pertanahan Nasional Republik Indonesia - Kurnia Rheza Randy Adinegoro (Jurnal Ilmu Kenotariatan, 2023)
The development of technology and communication systems in the world is currently growing rapidly. This technological advancement brings various impact changes. All sectors in life are starting to be touched by digital transformation, both in the private sector and the public sector. One of the public sector service providers in the field of land, the Ministry of Agrarian Affairs and Spatial Planning/National Land Agency has responded positively to digital transformation. This is realized by transforming land services, one of which is the transformation of Land Rights Certificates which were previously carried out conventionally to be transformed electronically. This research method is a normative juridical research method, namely a method that is carried out by studying and analyzing laws and regulations or other legal documents that are relevant to the problem to be studied. The data collection model is based on library research. This study tries to describe descriptively how the terminology of legal regulation regarding electronic certificates. The following discussion discusses the challenges of implementing electronic certificates and how the settlement efforts are carried out by the Ministry of ATR/BPN The results of this study found several challenges in implementing electronic certificates. These challenges include Infrastructure, Limited Community Capacity, Cyber Security, Digital Literacy Gaps and Data Privacy Issues. This paper also discusses the response of the ATR/BPN Ministry in facing these implementation challenges. KEYWORDS: Land Certificate, Electronic Land Certificate, Digital Transformation.